2014
DOI: 10.1016/j.resmic.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The recA operon: A novel stress response gene cluster in Bacteroides fragilis

Abstract: Bacteroides fragilis, an opportunistic pathogen of humans, is a leading cause of bacteraemias and anaerobic abscesses which are often treated with metronidazole, a drug which damages DNA. This study investigated the responses of the B. fragilis recA three gene operon to the stress experienced during metronidazole treatment and exposure to reactive oxygen species simulating those generated by the host immune system during infection. A transcriptionally regulated response was observed using quantitative RT-PCR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…116 Studies with Bfr by Nicholson et al suggested that the bacterioferritin co-migratory protein, encoded within the recA operon, may play a role in maintaining metabolic fitness and genomic integrity in response to oxidative stress. 117 This may be accomplished by assisting in the reduction of hydroperoxides, thereby preventing lipid oxidation and DNA damage during oxidative stress.…”
Section: Oxidative Stress Responses As Virulence Factors and Protectimentioning
confidence: 99%
“…116 Studies with Bfr by Nicholson et al suggested that the bacterioferritin co-migratory protein, encoded within the recA operon, may play a role in maintaining metabolic fitness and genomic integrity in response to oxidative stress. 117 This may be accomplished by assisting in the reduction of hydroperoxides, thereby preventing lipid oxidation and DNA damage during oxidative stress.…”
Section: Oxidative Stress Responses As Virulence Factors and Protectimentioning
confidence: 99%
“…Repair proteins such as MutS (EMQU_2803) conferring DNA mismatch repair and its protection from oxidative stress are slightly upregulated). So is the recA (EMQU_2752: 2 folds in the foregut) operon that was shown to be upregulated during oxidative stress (38); recF for recombination repair (39), whose general role is maintenance of DNA is upregulated (2 and 3 folds in fore- and hindguts, respectively) (40).…”
Section: Resultsmentioning
confidence: 99%
“…We also investigated the functional potential of susceptible microbiota and found genes regulating mRNA stability as a predictor of susceptibility. Response to stress caused by antibiotics involves changes in the transcriptional state of the bacteria [44], particularly elevated synthesis of selected stress response proteins [45,46]. To achieve this regulation, it is thought that keeping a low general mRNA abundance allows crucial mRNA encoding stress-related proteins to gain access to ribosomes for translation [47,48] short chain fatty acids [38], which have numerous health benefits for the host [55,56].…”
Section: Discussionmentioning
confidence: 99%